Relation Between Encapsulation of Streptococci of Serological Group B and Adherence Properties of The Bacteria to Deae-Sephacel - Christoph Lammler; I Wayan Teguh Wibawan; Fachriyan H Pasaribu (Media Veteriner, 1998)
Determination of surface charge of group B streptococci by ion exchange chromatography on DEAE-Sephacel revealed that bovine and human group B streptococcal isolates with protein surrface antigens alone, or bacteria with protein antigen in combination with polysacharide antigens, adhered strongly to the gel matrix. In contrary, cultures with polysacchaide antigens alone showed no comparable adherence properties. Removal of neuraminic acid from bacterial surface enhanced, but pronase treatment reduced the adherence values. The importance of type specific capsular sialylation for group B streptococcal surface charge could be confirmed with group B streptococci of serotype III and their transposon mutagenized asialocapsular mutants. In contrary to the encapsulated parent strains the asialo capsular mutants adhered strongly to the gel matrix. Comparable differences were observed with unencapsulated group B streptococcal variant strains and its isogenic encapsulated parent strains. The capsule material seemed to mask the surface proteins responsible for the adherence to the gel matrix. The determination of surface charge of group B streptococci by ion exchange chromatography might help to understand the importance of capsular sialylation for individual isolates of this bacterial species.